Emotions through time from antiquity to Byzantium - Cairns, Douglas L. 1961-; Hinterberger, Martin; Pizzone, Aglae 1976-; Zaccarini, Matteo (Emotions in Antiquity, 2022)
Introduction -- Douglas Cairns - A. Emotions through time? -- Douglas Cairns - B. Emotion research in Classics -- Martin Hinterberger and Aglae Pizzone - C. Research on emotions in the Byzantine world -- Douglas Cairns, Martin Hinterberger, and Aglae Pizzone - D. Chapter summaries -- Part I: Philosophy and Religion -- Andrea Capra - 1. Philosophy as a Chain of 'Poetic' Emotions? Plato and Beyond -- Divna Manolova - 2. Wondrous Knowledge and the Emotional Responses of Late Byzantine Scholars to Its Acquisition -- Petra von Gemünden - 3. Methodological Issues and Issues of Content , as Exemplified by ὀξυχολία in the Shepherd of Hermas -- Part II: Rhetorical Theory and Practice -- Byron MacDougall - 4. Lend a Sympathetic Ear: Rhetorical Theory and Emotion in Late Antique and Byzantine Homiletic -- Aglae Pizzone - 5. Emotions and λόγος ἐνδιάθετος: Πάθη in John Sikeliotes' Commentary on Hermogenes' On Types of Style -- Floris Bernard - 6. Emotional Communities in the Eleventh Century: Bodily Practices and Emotional Scripts -- Jan R. Stenger - 7. 'Aren't You Afraid That You Will Suffer the Same?': Emotive Persuasion in John Chrysostom's Preaching -- Niels Gaul - 8. Voicing and Gesturing Emotions: Remarks on Emotive Performance from Antiquity to the Middle Byzantine Period -- Part III: Literature -- Douglas Cairns - 9. Mental Conflict from Homer to Eustathius -- Mircea Graţian Duluş - 10. Ekphrasis and Emotional Intensity in the Homilies of Philagathos of Cerami -- Margaret Mullett - 11. Tragic Emotions? The Christos Paschon -- Martin Hinterberger - 12. Alazoneia and Aidōs/Aischunē in Anna Komnene's and Niketas Choniates' Histories -- Stavroula Constantinou - 13. Angry Warriors in the Byzantine War of Troy -- Part IV: Art and Ritual.